Optimization of sizing and energy management in hybrid energy storage systems for transient suppression in ship power systems under adverse sea conditions - Yu Ding; Shengping Ma; Guozheng Liu; Congbiao Sui; La Xiang (International Journal of Electrical Power & Energy Systems, 2025)
In adverse sea conditions, the ship Integrated Power System (IPS) will be subjected to significant load fluctuations, which has a serious impact on the safety of ship sailing and the power quality of shipboard electrical network. In this paper, the potential performance of Hybrid Energy Storage System (HESS), consisting of the battery and supercapacitor, in mitigating fluctuations in shipboard electrical network has been investigated based on the simulation model. To achieve a cooperative control among the three-source powertrains (i.e., the generation set system, Li-ion battery, and supercapacitor), a power distribution strategy is proposed. Considering that the power distribution and capacity sizing of HESS are highly related to each other, a multi-objective joint optimization method based on Multi-objective pelican optimization algorithm is proposed to obtain the optimal number of Li-ion battery and supercapacitor and the optimal power distribution strategy among the three-source powertrain for adverse sea conditions. The results indicate that the HESS can effectively mitigate fluctuations in frequency and voltage of AC bus, which are caused by the power supply side and/or the load side. Compared to the original IPS (without HESS), the fluctuations amplitude of frequency and voltage for the proposed IPS with optimal HESS are reduced by 63.0% and 74.5% in adverse sea conditions, effectively improving the electricity quality and safety of the ship. Moreover, compared to traditional optimization methods, the investment cost and installation space for the proposed IPS with optimal HESS are reduced by 53.9% and 54.2% respectively.